Molecular mapping of stem and leaf rust resistance in wheat - Khan, R. R.; Bariana, Harbans S.; Dholakia, Bhushan B.; Naik, S. V.; Lagu, Meena D.; Rathjen, A. J.; Bhavani, Sridhar; Gupta, V. S. (Theoretical and Applied Genetics, 2005)
Stem rust caused by Puccinia graminis f. sp. tritici Eriks and Henn and leaf rust caused by Puccinia triticina Rob. ex Desm. are major constraints to wheat production worldwide. In the present study, F-4-derived SSD population, developed from a cross between Australian cultivars `Schomburgk' and `Yarralinka', was used to identify molecular markers linked to rust resistance genes Lr3a and Sr22. A total of 1,330 RAPD and 100 ISSR primers and 33 SSR primer pairs selected on the basis of chromosomal locations of these genes were used. The ISSR marker UBC 840(540) was found to be linked with Lr3a in repulsion at a distance of 6.0 cM. Markers cfa2019 and cfa2123 flanked Sr22 at a distance of 5.9 cM (distal) and 6.0 cM (proximal), respectively. The use of these markers in combination would predict the presence or absence of Sr22 in breeding populations. A previously identified PCR-based diagnostic marker STS638 linked to Lr20 was validated in this population. This marker showed a recombination value of 7.1 cM with Lr20.